The safety and effectiveness of robot-assisted versus laparoscopic TME in patients with rectal cancer: A meta-analysis and systematic review. Issue 29 (July 2017) - Li, Xiaofei; Wang, Tao; Yao, Liang; Hu, Lidong; Jin, Penghui; Guo, Tiankang; Yang, Kehu
Abstract: Background: The aim of this study was to assess the safety and effectiveness of robotic-assisted versus laparoscopic total mesorectal excision (TME) in patients with rectal cancer. Methods: We systematically searched PubMed, EMBASE, Cochrane library, Web of science, and Chinese Biomedical Literature Database up to July 2016 to identify case-controlled studies that compared robotic TME (RTME) with laparoscopic TME (LTME) for rectal cancer. GRADE was used to interpret the primary outcomes of this meta-analysis. Results: We included 17 case–control studies (3601 participants: 1726 underwent RTME and 1875 LTME for rectal cancer) that compared RTME with LTME for rectal cancer. We found no statistically significant differences between techniques for local recurrence [odds ratio (OR) = 0.68, P  = .216] and overall survival at 3 years (OR = 0.71, P  = 1.140), complications (OR = 1.02, P  = .883), positive circumferential resection margin (PCRM) (OR = 0.80, P  = .256), the first passing flatus [weighted mean difference (WMD) = −0.11, P  = .130], reoperation (OR = 0.66, P  = .080), estimated blood loss (EBL) (WMD = −12.45, P  = .500), and length of stay in hospital (LOS) (WMD = −0.69, P  = .089). Compared with LTME, RTME was associated with lower rate of conversion (OR = 0.35, P  < .001), urinary retention (OR = 0.41, P  = .025), and longer operative time (WMD = 57.43, P  < .001). The overall quality of evidence was poor in all outcomes. Conclusion: RTME in patients with rectal cancer was associated with a lower rate of conversion and less incidence of urinary retention. Generally, operative time in RTME was significantly longer than in LTME. The long-term oncological and function outcomes of RTME seem to be equivalent with LTME. Therefore, analysis of current studies to date did not indicate a major benefit of RTME over LTME.